URGENSI KOMPETENSI GURU - Suraji, Imam (Forum Tarbiyah, 2012)
Teacher is professional educator who has been trusted by society to educate and guide their children. As professional educator, teacher must fulfill some requirements that has been stated. One of them is having four comptences, i.e. paedagogy, personality,   professional, and social competence. The competences are needed because the task of the teacher does not only transform knowledge, technology, and skill but also builds character of their student. With the competence teacher will be able to educate and guide his students well, so that they cancontinue and complete the struggle of their parents and nation in the future